Transcranial direct current stimulation in mild cognitive impairment: Behavioral effects and neural mechanisms. Issue 9 (20th November 2014) - Meinzer, Marcus; Lindenberg, Robert; Phan, Mai Thy; Ulm, Lena; Volk, Carina; Flöel, Agnes
Abstract : Introduction: The long preclinical phase of Alzheimer's disease provides opportunities for potential disease‐modifying interventions in prodromal stages such as mild cognitive impairment (MCI). Anodal transcranial direct current stimulation (anodal‐tDCS), with its potential to enhance neuroplasticity, may allow improving cognition in MCI. Methods: In a double‐blind, cross‐over, sham‐controlled study, anodal‐tDCS was administered to the left inferior frontal cortex during task‐related and resting‐state functional magnetic resonance imaging (fMRI) to assess its impact on cognition and brain functions in MCI. Results: During sham stimulation, MCI patients produced fewer correct semantic‐word‐retrieval responses than matched healthy controls, which was associated with hyperactivity in bilateral prefrontal regions. Anodal‐tDCS significantly improved performance to the level of controls, reduced task‐related prefrontal hyperactivity and resulted in "normalization" of abnormal network configuration during resting‐state fMRI. Discussion: Anodal‐tDCS exerts beneficial effects on cognition and brain functions in MCI, thereby providing a framework to test whether repeated stimulation sessions may yield sustained reversal of cognitive deficits.